Os 50 anos do movimento de cursilhos de cristandade da Diocese de Uruguaiana: uma história de evangelização - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This report is part of an experimental project realized as an end of course paper with the overall goal to develop a non-fiction book about the history of the Catholic Church's Movement called Cursillos, created in 1940 in Spain, brought to Brazil in 1962, and then to a Diocese in the west of the state of Rio Grande do Sul in 1975. The theme was chosen due to the necessity to document the history of the Movement that spread to the region and conquered members that lived part of this construction. To make the non-fiction book, 15 interviews were conducted with people who were part of the four most important moments of this history: the beginning of the Movement, the pause of the retreats, the comeback, the creation of a retreat for young people, and the present time. The paper development had bibliographical research and methodology (defined by pre-production, production and post-production), resulting in a non-fiction book with 81 pages, including the cover and supporters.
The 50th anniversary of the Cursillo movement in the Diocese of Uruguaiana: a history of evangelization
Keywords: Livro-reportagem; Igreja Católica; Testemunho; Non-fiction Book; Catholic Church; Testimony; CIENCIAS SOCIAIS APLICADAS